Age-related differences in IgE between childhood and adulthood allergic asthma: Analysis of NHANES 2005–2006 - Heping Fang, MMeD; Juan Li, MMeD; Luo Ren, MD, PhD; Enmei Liu, MD, PhD (World Allergy Organization Journal, 2023)
Background: Asthma exhibits varying clinical features in children and adults. However, previous studies have mainly focused on the clinical significance of immunoglobulin E (IgE) in the diagnosis and treatment of asthma, disregarding the characteristics of IgE and its relevant factors. Objective: This study aimed to gain a better understanding of the differences in the characteristics of IgE between childhood and adulthood allergic asthma (AA). Methods: Patients with AA from the 2005 to 2006 National Health and Nutrition Examination Survey (NHANES) were divided into 3 groups based on their current age and onset age of AA: childhood AA (Group 1), childhood-onset adult AA (Group 2), and adulthood-onset AA (Group 3). Intragroup analysis and intergroup comparison were carried out, focusing on the characteristics and relevant factors of IgE, as well as the clinical relevance of total IgE (total IgE, tIgE) and allergen-specific IgE (allergen-specific IgE, sIgE). Results: A total of 424 patients were analyzed, including 187 with childhood AA, 132 with childhood-onset adult AA, and 105 with adulthood-onset AA. The concentration of tIgE was found to be higher in Group 1 (268.0, 118.0–686.0 kU/L) than in Group 2 (224.0, 78.0–494.0 kU/L) and Group 3 (165.0, 74.4–350.5 kU/L). The sensitization rates did not differ between Group 1 and Group 2 but were higher compared with Group 3, particularly for Alternaria-sIgE (50.3% and 46.2% vs 15.2%) and Aspergillus-sIgE (43.9% and 37.1% vs 16.2%). In Group 1, there was a negative correlation between pollen-sIgEs and indoor allergens, but this correlation was not commonly observed in Group 2 and Group 3. On the other hand, in Group 1, environmental chemicals such as phthalates, polyaromatic hydrocarbons, trihalomethanes, and phenols showed a positive correlation with IgE. However, a greater number of chemicals was observed in Group 2 and Group 3, including cotinine, metals, trihalomethanes, phthalates, phenols, and other volatile organic compounds (VOCs). Furthermore, in Group 1, IgE was positively correlated with asthma-related issues such as emergency visits, absenteeism, limited activities, and medication needs. These correlations were less common in Group 2 and Group 3, particularly in Group 3. Conclusions: There are notable differences in the characteristics and environmental factors of IgE among childhood AA, childhood-onset adult AA, and adulthood-onset AA. Additionally, IgE plays a more significant role in childhood AA due to its higher concentration, fewer relevant environmental chemicals and greater clinical relevance. This may partially explain the age-related features of asthma.